The Global Acceptance and Development of Probiotic-Containing Products as Functional Food - Thu, Dao Thi Anh (Global and Policy Journal of International Relations, 2013)
ABSTRACTProbiotics have been associated with a range of health benefits and have been made available to the consumers via a range of functional food products. However, it has showed that there still a gap between countries in the acceptance to health benefits of probiotics. The national variation in the acceptance and awareness of consumers to probiotic-containing products have affected greatly to the different development of probiotic markets in the world. The global market for this type of functional foods in the coming years is expected to increase significantly. The Asia in general and Japan in particular still is the major market, whereas Europe countries and the US market obtain quickly rate of growth. Several factors affecting the success of probiotic-containing products also are indicated to achieve greater popularity of this type of functional foods.Keywords: probiotics, prebiotics, microencapsulation, functional food, potential market.DOI:https://doi.org/10.33005/jgp.v1i02.1992